Study on Yogyakarta Special Territory Government’s Policy on HIV-AIDS Prevention - Warto Warto; Chatarina Rusmiyati (Media Informasi Penelitian Kesejahteraan Sosial, 2015)
The study on HIV-AIDS prevention conducted in Yogyakarta Special Territory, as a territory of epidemic consentration and governmental commitment on HIV-AIDS prevention.  The goal of the study is to get a description on the implementation of HIV-AIDS prevention policy, including its handicap and supporting factors. This study is qualitative-descriptive. Data are gathered from KPA activity document and several researchs on those subjects to describe Yogyakarta Special Territory policy implementation, and suppoted from interview result with several managements. The result shows that HIV-AIDS started with Local Regulation No 12, 2010 on HIV-AIDS prevention and Governor Regulation No 39, 2012 on HIV-AIDS prevention commission, followed by Deputy Governor Rulling on member definition section. Those regulation implemented through setting and strategy action planning, HIV-AIDS socialization at Local Education Agency and Territorial Representative  of  Religius Ministry, HIV-AIDS curriculum application try-out in schools, personels of HIV-AIDS victims shelter training, giving HIV-AIDS pocket books for teachers, and set an institution for people commited in HIV-AIDS prevention in each subdistrict, and several research results on HIV-AIDS prevention. The local government strong commitment in facilitating several activities on HIV-AIDS prevention is a supporting factor, while the handicap of HIV-AIDS prevention policy implementation is the limit of fund to implement the action plan, especially research activity as a base for policy reference. There have been yet all institutions supporting prevention policy, the activities have been done are not to the right target and its result is still not yet optimum. Based on that study, it is recommended that action plan implementation should be reached wider to all institutions participation, sort of government,coorporation, community element, and will be more accurate if all the policies based on research results.